Conditional mutagenesis of a novel choline kinase demonstrates plasticity of phosphatidylcholine biogenesis and gene expression in Toxoplasma gondii - Sampels, Vera; Hartmann, Anne; Dietrich, Isabelle; Coppens, Isabelle; Sheiner, Lilach; Striepen, Boris; Herrmann, Andreas; Lucius, Richard; Gupta, Nishith (The Journal of biological chemistry, 2012)
The obligate intracellular and promiscuous protozoan parasite Toxoplasma gondii needs an extensive membrane biogenesis that must be satisfied irrespective of its host-cell milieu. We show that the synthesis of the major lipid in T. gondii, phosphatidylcholine (PtdCho), is initiated by a novel choline kinase (TgCK). Full-length (∼70-kDa) TgCK displayed a low affinity for choline (K(m) ∼0.77 mM) and harbors a unique N-terminal hydrophobic peptide that is required for the formation of enzyme oligomers in the parasite cytosol but not for activity. Conditional mutagenesis of the TgCK gene in T. gondii attenuated the protein level by ∼60%, which was abolished in the off state of the mutant (Δtgck(i)). Unexpectedly, the mutant was not impaired in its growth and exhibited a normal PtdCho biogenesis. The parasite compensated for the loss of full-length TgCK by two potential 53- and 44-kDa isoforms expressed through a cryptic promoter identified within exon 1. TgCK-Exon1 alone was sufficient in driving the expression of GFP in E. coli. The presence of a cryptic promoter correlated with the persistent enzyme activity, PtdCho synthesis, and susceptibility of T. gondii to a choline analog, dimethylethanolamine. Quite notably, the mutant displayed a regular growth in the off state despite a 35% decline in PtdCho content and lipid synthesis, suggesting a compositional flexibility in the membranes of the parasite. The observed plasticity of gene expression and membrane biogenesis can ensure a faithful replication and adaptation of T. gondii in disparate host or nutrient environments.